Factors affecting the rare earth element compositions in massive sulfides from deep‐sea hydrothermal systems. (21st August 2015) - Zeng, Zhigang; Ma, Yao; Yin, Xuebo; Selby, David; Kong, Fancui; Chen, Shuai
Abstract: To reconstruct the evolution of ore‐forming fluids and determine the physicochemical conditions of deposition associated with seafloor massive sulfides, we must better understand the sources of rare earth elements (REEs), the factors that affect the REE abundance in the sulfides, and the REE flux from hydrothermal fluids to the sulfides. Here we examine the REE profiles of 46 massive sulfide samples collected from seven seafloor hydrothermal systems. These profiles feature variable total REE concentrations (37.2–4092 ppb) and REE distribution patterns (LaCN /LuCN ratios = 2.00–73.8; (Eu/Eu*)CN ratios = 0.34–7.60). The majority of the REE distribution patterns in the sulfides are similar to those of vent fluids, with the sulfides also exhibiting light REE enrichment. We demonstrate that the variable REE concentrations, Eu anomalies, and fractionation between light REEs and heavy REEs in the sulfides exhibit a relationship with the REE properties of the sulfide‐forming fluids and the massive sulfide chemistry. Based on the sulfide REE data, we estimate that modern seafloor sulfide deposits contain approximately 280 t of REEs. According to the flux of hydrothermal fluids at mid‐ocean ridges (MORs) and an average REE concentration of 3 ng/g in these fluids, hydrothermal vents at MORs alone transport more REEs (>360 t) to the oceans over the course of just 2 years than the total quantity of REEs in seafloor sulfides. The excess REEs (i.e., the quantity not captured by massive sulfides) may be transported away from the systems and become bound in sulfate deposits and metalliferous sediments. Key Points: Hydrothermal fluids are significant sources of REEs in seafloor massive sulfides Sulfide‐forming fluids and mineral chemistry jointly affect sulfide REE patterns Global seafloor sulfide deposits contain approximately 280 t of REEs